Ornament and Nonsense. Wittgenstein’s architecture and Wittgenstein’s early philosophy - Henriques, Raimundo Ferreira (2022)
Between 1926 and 1928, the philosopher Ludwig Wittgenstein designed a house for his sister in Vienna (the Kundmanngasse). This thesis aims at clarifying the relation between that house and Wittgenstein’s early philosophy. I will argue that the connection between them ought to be construed in an indirect manner, giving equal importance to the interpretation of Wittgenstein’s Tractatus Logico-Philosophicus (1921/1922) and his cultural milieu. I will start by providing some background information and an overview of what has been said on the subject. I will then turn to a remark from Diktat für Schlick (c. 1932) where Wittgenstein proposes an analogy between ornaments and nonsensical sentences. Using this analogy as a clue, I will address the hypothesis that the Kundmanngasse was designed within an architectural equivalent of the sign-language envisaged in the Tractatus. I will take this hypothesis as far as possible and conclude that it is not promising. I will then go back to the analogy and, following Wittgenstein’s parenthetical recognition of his influence, turn to Adolf Loos’s writings. This will provide a different way of understanding the analogy, focused, not on actual ornaments and nonsensical sentences, but on how Loos and Wittgenstein use the notions. I will argue that, so understood, the analogy favors the (so-called) resolute reading of the Tractatus. I will then turn to Wittgenstein’s remarks on architecture and argue that he and Loos endorsed a qualified form of architectural functionalism. This will allow me to claim that the connection between the Kundmanngasse and the Tractatus lies in both being the result of Wittgenstein’s striving for self-understanding and improvement.